Students’ violation of cooperative principle in thesis exams - Mohammad Muhassin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
This study aims to find out and describe the maxim of conversation  most violated by students and the types of maxim violation in thesis exams. This  is a kind of descriptive  qualitative  research.  The  data  are utterances containing maxim violations by the students in thesis exams at the department of English education, Faculty of Education and Teacher Training, State Islamic University of Raden Intan Lampung in 2018/2019 academic year. The researcher used  a documentation method of the recordings of students’ thesis exams,  and   a note-taking  technique  in collecting the data. The result of the research  shows  that among the 13 utterances, quantity maxim was violated most with 5 utterances (38.46%), subsequently followed by relation maxim with 4 utterances (30.76%). Meanwhile both quality and manner maxims placed the third maxims most violated by the students, each with 2 utterances (15.38%) respectively. In addition, maxims of quantity, quality, relation, and manner are violated by the students in thesis exams, namely quantity, quality, relation, and manner maxims. The violations are in the form of exaggerated information for quantity maxim, untrue information for quality maxim, irrelevant information for relation maxim, and confusing information for manner maxim.